Homologie des invariants d'une algèbre de Weyl sous l'action d'un groupe fini - Alev, J. (2000)
Soit G un sous-groupe fini de Sp(2n,C) opérant par automorphismes dans l'algèbre de Weyl An(C). Nous calculons les groupes d'homologie et de cohomologie de Hochschild de l'algèbre d'invariants An(C)G. Let G be a finite subgroup of Sp(2n,C) acting by automorphisms in the Weyl algebra An(C). We compute the Hochschild homology and cohomology groups of the invariant algebra An(C)G. © 2000 Academic Press.